Aktivitas antioksidan ekstrak etanol rimpang curcuma xanthorrhiza roxb. Dan asam askorbat (Dengan Metode DPPH, ABTS, Dan NO) - Olivia Amanda Suwardi; Monica Dewi Ranggaini (Fakultas Kedokteran Gigi Universitas Trisakti, 2022)
Background: Antioxidants are very important to prevent degenerative diseases. Natural ingredients used as natural antioxidants are C. xanthorrhiza Roxb. Purpose: To compare antioxidant activity between ethanol extract C. xanthorrhiza Roxb. and ascorbic acid with DPPH, ABTS, and NO methods. Methods: Experimental laboratory research. C. xanthorrhiza Roxb. was extracted by maceration method. In the DPPH, ABTS, and NO methods, C. xanthorrhiza Roxb. and ascorbic acid were incubated. Then the absorbance was measured at a wavelength 517 nm for the DPPH method, 745 nm for the ABTS method, and 516 nm for NO method. Results: In DPPH method, IC50 of ethanol extract C. xanthorrhiza Roxb. was 194.74 g/mL and 0.29 g/mL for ascorbic acid, in ABTS method IC50 of ethanol extract C. xanthorrhiza Roxb. was 80.04 g/mL and 2.49 g/mL for ascorbic acid, in NO method, IC50 of ethanol extract C. xanthorrhiza Roxb. was 164.11 g/mL and 0.54 g/mL for ascorbic acid. Conclusion: In DPPH and NO methods, C. xanthorrhiza Roxb. has weak antioxidant activity and in ABTS method has strong antioxidant activity. In DPPH, ABTS, and NO methods, ascorbic acid has very strong antioxidant activity.